Professional Development Programs and Teacher Effectiveness in Government Aided Secondary Schools in Ibanda Municipality. - Mwesigye, Seriano (Kabale University, 2023)
The aim of the study was to establish the effect of Professional Development Programs (PDPs) on Teacher Effectiveness in selected schools in Ibanda Municipality. The study adopted across-sectional survey design with mixed research approaches of data collection and analysis. The study population included 3 participants from Ibanda municipal education office, 6 headteachers and 122 teachers from Government-Aided Secondary Schools in Ibanda Municipality. Questionnaire and interview guide were used to collect data. Quantitative data was analyzed using statistical package for social sciences (SPSS 20.0) while content analysis was used for the analysis of qualitative data. Among others, the key finding from the study include: school administrators do not usually organize induction workshops for new teachers, no formal Induction program for new teachers in the selected schools, school administrators in Ibanda Municipality did not regularly organize orientation seminars for new teachers, teachers have negative attitudes towards PDPs, the schools lack funds to support teachers undertaking PDPs, and that most PDPs are not properly planned and are not evaluated to ascertain the effectiveness. The study recommends that there should be a policy on professional development programs in secondary schools in Ibanda Municipality by the Ibanda Municipality Education Office. There is need to maintain and improve on teachers’ effectiveness by increasing on their knowledge, skills, and abilities through provision of professional development programs.